Hematopoietic colony-stimulating factors: new players in tumor-nerve interactions - Stösser, Sebastian; Schweizerhof, Matthias; Kuner, Rohini (Journal of molecular medicine, 2011)
A variety of cancers are accompanied by debilitating pain, which constitutes the primary reason for poor quality of life in cancer patients. There is an urgent demand for the development of specific mechanism-based therapies against cancer pain. Recently, important advances have been made in mechanisms contributing to cancer pain. A notable finding was that the tumor-derived hematopoietic growth factors, granulocyte- and granulocyte-macrophage-colony-stimulating factors (G-CSF/GM-CSF), subserve important functions in the generation of pain hypersensitivity in tumor-affected regions. In this context, their receptors were unexpectedly found on pain-sensing nerves and were observed to be functionally linked to nociceptive sensitization and tumor-induced pain. Here, we review evidence supporting a role for G-/GM-CSF in sensitization of pain-sensing nerves, the underlying signaling pathways and the cross-talk with other pronociceptive cytokines, peptides and modulators derived from immune cells, osteoclasts and tumor cells. These findings hold implications in the therapy of pain in disease states, such as cancer and rheumatoid arthritis.